From the PnTx2-6 Toxin to the PnPP-19 Engineered Peptide: Therapeutic Potential in Erectile Dysfunction, Nociception, and Glaucoma - Silva, Carolina Nunes da; Nunes, Kenia Pedrosa; Dourado, Lays Fernanda Nunes; Vieira, Thayllon Oliveira; Mariano, Xavier Maia; Cunha Junior, Armando da Silva; de Lima, Maria Elena (Frontiers in Molecular Biosciences, 2022)
The venom of the “armed” spider Phoneutria nigriventer comprises several potent toxins. One of the most toxic components from this venom is the neurotoxin PnTx2-6 (LD50 = 0.7 μg/mouse, 48 residues, five disulfide bridges, MW = 5,289.31 Da), which slows down the inactivation of various Na+ channels. In mice and rats, this toxin causes priapism, an involuntary and painful erection, similar to what is observed in humans bitten by P. nigriventer. While not completely elucidated, it is clear that PnTx2-6 potentiates erectile function via NO/cGMP signaling, but it has many off-target effects. Seeking to obtain a simpler and less toxic molecule able to retain the pharmacological properties of this toxin, we designed and synthesized the peptide PnPP-19 (19 residues, MW = 2,485.6 Da), representing a discontinuous epitope of PnTx2-6. This synthetic peptide also potentiates erectile function via NO/cGMP, but it does not target Na+ channels, and therefore, it displays nontoxic properties in animals even at high doses. PnPP-19 effectively potentiates erectile function not only after subcutaneous or intravenous administration but also following topical application. Surprisingly, PnPP-19 showed central and peripheral antinociceptive activity involving the opioid and cannabinoid systems, suggesting applicability in nociception. Furthermore, considering that PnPP-19 increases NO availability in the corpus cavernosum, this peptide was also tested in a model of induced intraocular hypertension, characterized by low NO levels, and it showed promising results by decreasing the intraocular pressure which prevents retinal damage. Herein, we discuss how was engineered this smaller active nontoxic peptide with promising results in the treatment of erectile dysfunction, nociception, and glaucoma from the noxious PnTx2-6 toxin, as well as the pitfalls of this ongoing journey.